Correction: Spatial regulation of Drosophila ovarian Follicle Stem Cell division rates and cell cycle transitions - Melamed, David; Choi, Aaron; Reilein, Amy; Tavaré, Simon; Kalderon, Daniel (PLoS genetics, 2023)
[This corrects the article DOI: 10.1371/journal.pgen.1010965.].